2017
DOI: 10.5194/hess-21-4973-2017
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater propagation through snowpack during rain-on-snow sprinkling experiments under different snow conditions

Abstract: Abstract. The mechanisms of rainwater propagation and runoff generation during rain-on-snow (ROS) events are still insufficiently known. Understanding storage and transport of liquid water in natural snowpacks is crucial, especially for forecasting of natural hazards such as floods and wet snow avalanches. In this study, propagation of rainwater through snow was investigated by sprinkling experiments with deuterium-enriched water and applying an alternative hydrograph separation technique on samples collected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
(81 reference statements)
1
14
0
Order By: Relevance
“…Understanding the scale of intra-snowpack flow paths is also important for understanding the physical run-off generation during rain-on-snow events that are likely to increase in frequency in the future (Musselman et al, 2018). A significant factor in run-off quantity and timing from rain-on-snow events is the antecedent intrasnowpack liquid water storage (Juras, Würzer, Pavlasek, Vitvar, & Jonas, 2017;Würzer et al, 2016). Thus, the antecedent intrasnowpack LWC storage that may be obtained using the methods of this study could prove beneficial for flood planning purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the scale of intra-snowpack flow paths is also important for understanding the physical run-off generation during rain-on-snow events that are likely to increase in frequency in the future (Musselman et al, 2018). A significant factor in run-off quantity and timing from rain-on-snow events is the antecedent intrasnowpack liquid water storage (Juras, Würzer, Pavlasek, Vitvar, & Jonas, 2017;Würzer et al, 2016). Thus, the antecedent intrasnowpack LWC storage that may be obtained using the methods of this study could prove beneficial for flood planning purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, within the snowpack, certain processes remain difficult to assess. Würzer et al (2017) and Juras, Würzer, Pavlásek, Vitvar, and Jonas (2017) showed that preferential vertical flow of liquid water within a snowpack considerably influences rain water retention. Eiriksson et al (2013) further revealed the importance of preferential lateral flow in sloped terrain for runoff formation in complex topography.…”
Section: Results In the Context Of Hydrological Modellingmentioning
confidence: 99%
“…This was because there was no extreme rain‐on‐snow event which would supply a significant amount of liquid water into the snowpack. However, this heat exchange might be important when assessing the energy balance at daily and shorter temporal resolutions (Juras, Würzer, Pavlasek, Vitvar, & Jonas, 2017; Würzer et al, 2016). In general, rain input might be a significant heat flux for basins with air temperature fluctuating near the freezing point during winter months and thus rain events occur more often.…”
Section: Discussionmentioning
confidence: 99%